Vamos a atividade do dia: o acerto de contas no trabalho do tráfico de drogas varejista - Thaisa Vilela Fonseca Amaral (2014)
Drug trafficking takes, every day, a larger space of everyday life as a representative of a supposed civil war that was ravaging our society. The daily news creates associative lines sticking the image of the drug dealer to the production and dissemination of evil showing justifications that elevate the status of enemy to be fought. The assignment of a malignant character, sometimes pathological, which culminates in a process of demonization of dealer conceals a discursive construction guided by a radical distinction between good and evil. Despite these dualistic conceptions, drug trafficking was set up in recent decades, as an important activity that generates capital through the mercantilization of illicit drugs. In this sense, appears as a labor organization that occurs in the field of illegality. Thus, sustained in theoretical / methodological perspective of Labour Psychology we try to analyze, in this paper, the operation of retail drug trafficking in a microregion of Minas Gerais seeking to understand the activity of "payback". In a qualitative approach, we work with interviews with people who were involved in drug trafficking in retail and observation, which we will call here as engaged observation. Also we attended, for a period of four months, a workshop of grafite, which occurred near a point of the illicit drug trade, with the sole purpose of genuinely experience, surprising freely and implicated the studied reality. The results obtained in the research emphasized a scenario where the killing is naturalized, instrumentalized and spectacularized with significant implications for the structuring of a labor organization and recognition of their workers. The use of lethal violence in the payback, which for decades has been connected to private vengeance, followed the format changes in the management of drug trafficking and seems currently correspond to a prescription of the job.